Relationship between gestational age and endoglin levels in maternal and cord blood - Kharb, Simmi; Tiwari, R.; Nanda, S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Poor placentation at early gestational age is an important predisposing condition for the development of preeclampsia. The present study was designed to study the relationship of gestational age with endoglin levels in maternal and cord blood of normal and pre-eclamptic women. Methods: The present study was conducted in fifty pregnant women that were grouped as: group 1 (control, n=25) comprising of normotensive women immediately after delivery, group 2 (study group, n=25) comprising of age -and sex- matched pre-eclamptic women. Study samples were drawn (maternal venous blood and umbilical cord blood). Endoglin was analyzed by competitive enzyme linked immunosorbent assay. Results: Maternal serum endoglin levels were decreased in group II as compared to group I. Maternal endoglin showed a positive correlation with gestational age in both normotensive and preeclamptic women. Cord blood endoglin showed negative correlation with gestational age in both normotensive women and preeclamptics. A significant positive correlation was found between maternal and cord blood endoglin levels with birth weight in preeclamptic mothers. Pre-eclamptics with birth weight less than 2.5 kg had lower maternal blood endoglin levels as compared to controls. Conclusions: These finding suggest that endoglin levels may responsible for the pathogenesis of PE and/or IUGR.